English English - Afrian F; Okfalisa (UIR PRESS, 2023)
A Decision-Making in determining the project tender winner becomes a significant challenge in the procurement stage, thus it is very vulnerable to administrative errors, corruption, and nepotism. Therefore, a recommendation system becomes a new problem solving in order to increase the information transparency, the company’s opportunity to win, the fraud minimization, and the community complaint on the project tender. The system is developed using the analysis of Fuzzy MOORA to calculate the significant consideration of six criteria, including the administration, the qualifications, the technical experience, the proposed price, the number of projects, and the size of the project based on the winning budget. Herein, 20 companies were acted as alternatives in applying and testing the recommendation tender system. As a result, Blackbox and User Acceptance Test (UAT) of this application from ten staffs of the Working Selection Group (POKJA) at the Bureau of Procurement of Goods and Services (PBJ) of Riau Province found that the entire modules and functions of the system run well. Meanwhile, UAT scores of 87.6% states that this application can assist the POKJA’s staffs in objectively selecting the tender winner. In addition, the sensitivity test analyzes the possible increasing of the weighting criteria, viz., C3 (technical experience) and C4 (price) can improve the quality rankings of alternatives up to 79.16%. Thus, this result enhanced the efficacy of Fuzzy MOORA approach in providing a better recommendation analysis.